Racial Disparity in Pregnancy Risks and Complications in the US: Temporal Changes during 2007–2018 - Bornstein, Eran (J Clin Med, 2020)
Maternal race and ethnicity have been associated with differences in pregnancy related morbidity and mortality. We aimed to evaluate the trends of several pregnancy risk factors/complications among different maternal racial/ethnic groups in the US between 2007 and 2018. Specifically, we used the Center for Disease Control and Prevention (CDC) natality files for these years to assess the trends of hypertensive disorders of pregnancy (HDP), chronic hypertension (CH), diabetes mellitus (DM), advanced maternal age (AMA) and grand multiparity (GM) among non-Hispanic Whites, non-Hispanic Blacks and Hispanics. We find that the prevalence of all of these risk factors/complications increased significantly across all racial/ethnic groups from 2007 to 2018. In particular, Hispanic women exhibited the highest increase, followed by non-Hispanic Black women, in the prevalence of HDP, CH, DM and AMA. However, throughout the entire period, the overall prevalence remained highest among non-Hispanic Blacks for HDP, CH and GM, among Hispanics for DM, and among non-Hispanic Whites for AMA. Our results point to significant racial/ethnic differences in the overall prevalence, as well as the temporal changes in the prevalence, of these pregnancy risk factors/complications during the 2007–2018 period. These findings could potentially contribute to our understanding of the observed racial/ethnic differences in maternal morbidity and mortality.